Implementasi Good Governance Dalam Pelayanan Publik Pada Kantor Kecamatan Balaraja - Dadang Rusdiana; Aryanti Dwi Untari (STKIP Subang, 2025)
This study aims to examine the implementation of good governance principles in public services at the Balaraja District Office, Tangerang Regency. The core principles of good governance focused on in this study are accountability, transparency, participation, and the rule of law. This research employed a descriptive qualitative method using interviews, observations, and documentation as data collection techniques. The findings indicate that the Balaraja District Office has implemented accountability through increased public trust in its services. Transparency is reflected in the availability of information via the official website and direct services. Public participation is facilitated through complaint channels and joint evaluation forums. Meanwhile, the rule of law is enforced through adherence to standard operating procedures (SOPs) and the application of sanctions for violations. Although there are shortcomings, such as limited information on the website, public service delivery has generally been carried out effectively. The implementation of these four principles supports the development of higher quality, accountable, and citizen-oriented public services. This research is expected to serve as an academic reference in the study of local governance systems and public service delivery.